Eutrophication weakens interspecific relationships across trophic levels in an urban wetland - Wei, Yingshan; Peng, He-Bo; Qi, Linhui; Cai, Yanpeng; Guo, Qingyang; Zhu, Zhenchang (Watershed ecology and the environment, 2025)
•Eutrophication weakens interspecific interactions across trophic levels while strengthening interspecific interactions within the same trophic level, especially among phytoplankton.•Water depth, manganese concentrations, and TSI are key drivers of species interactions in urban wetlands.•Environmental DNA (eDNA) and high-throughput sequencing provide a comprehensive analysis of trophic interactions under varying nutrient levels. Eutrophication poses a major threat to the stability of global aquatic ecosystems, especially in urban wetlands highly influenced by human activities. It frequently alters species composition, which in turn affects the overall structure of ecosystems. However, how eutrophication impacts inter-species interactions across different trophic levels remains poorly understood. This study examines communities at varying nutrient status within the same urban wetland, including phytoplankton, zooplankton, and fish, while considering environmental factors such as dissolved oxygen, manganese (Mn), water depth, and the Trophic State Index (TSI). We assess how eutrophication influences species interactions across multiple trophic levels. Our results show that intra-trophic correlations were primarily driven by water depth, manganese, whereas inter-trophic correlations were predominantly governed by TSI. Specifically, inter-group correlations between different trophic levels decreased with raising TSI, while inter-species relationships within phytoplankton strengthened with increasing TSI. These findings provide crucial insights into the mechanisms underlying species coexistence in urban wetlands and highlight the need for targeted management strategies to maintain ecological stability in the face of eutrophication. Future research should explore temporal and spatial dynamics to better understand the complex responses of wetland ecosystems to nutrient fluctuations.